Supplemental material for The impact of risk factor trends on intracerebral hemorrhage incidence over the last two decades—The Tromsø Study ... - Carlsson, Maria; Wilsgaard, Tom; Johnsen, Stein Harald; Liv-Hege Johnsen; Maja-Lisa Løchen; Njølstad, Inger; Mathiesen, Ellisiv Bøgeberg (SAGE Journals, 2018)
Supplemental material for The impact of risk factor trends on intracerebral hemorrhage incidence over the last two decades—The Tromsø Study by Maria Carlsson, Tom Wilsgaard, Stein Harald Johnsen, Liv-Hege Johnsen, Maja-Lisa Løchen, Inger Njølstad and Ellisiv Bøgeberg Mathiesen in International Journal of Stroke ...